2012
DOI: 10.3109/0886022x.2012.717484
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin E-Coated Membrane Dialyzer Compared to Simvastatin in Patients on Chronic Hemodialysis

Abstract: Background: We investigated the effects of the use of vitamin E-coated membrane (VEM) dialyzer in comparison to simvastatin on markers of chronic inflammation, oxidative stress, and endothelial cell apoptosis in ten patients on chronic hemodialysis (HD), aiming at distinguishing the different treatment effects and their time sequence on these pathogenetic routes. Methods: Ten HD patients were sequentially submitted to a 6-month treatment with the use of VEM and 10 mg of simvastatin daily, interrupted by a 3-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…5 Recently, we and others have shown that the use of cellulose-based VEM exert significant anti-inflammatory and antioxidative effects in patients on HD, 6,7 reflected mainly on decreases in the levels of serum C-reactive protein (CRP), interleukin-6 (IL-6, and plasma oxidized low-density lipoproteins (oxLDL). Similar findings with the use of a newer polysulfone-based VEM were more recently found by Panichi et al 8 Triggered by our observation that antioxidative effects of VEM are preceded by their anti-inflammatory effects, 6,9 we performed the present secondary analysis to assess the probable association of antioxidative effects of VEM with the baseline inflammatory status, controlling for other established risk factors as well, in HD patients.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…5 Recently, we and others have shown that the use of cellulose-based VEM exert significant anti-inflammatory and antioxidative effects in patients on HD, 6,7 reflected mainly on decreases in the levels of serum C-reactive protein (CRP), interleukin-6 (IL-6, and plasma oxidized low-density lipoproteins (oxLDL). Similar findings with the use of a newer polysulfone-based VEM were more recently found by Panichi et al 8 Triggered by our observation that antioxidative effects of VEM are preceded by their anti-inflammatory effects, 6,9 we performed the present secondary analysis to assess the probable association of antioxidative effects of VEM with the baseline inflammatory status, controlling for other established risk factors as well, in HD patients.…”
Section: Introductionsupporting
confidence: 78%
“…Similar findings with the use of a newer polysulfone‐based VEM were more recently found by Panichi et al . Triggered by our observation that antioxidative effects of VEM are preceded by their anti‐inflammatory effects, we performed the present secondary analysis to assess the probable association of antioxidative effects of VEM with the baseline inflammatory status, controlling for other established risk factors as well, in HD patients.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation